The optimal duration of ischemic preconditioning for renal ischemia-reperfusion injury in mice - Choi, Hyun Su (Ann Surg Treat Res, 2017)
PURPOSE: The aim of the present study was to investigate the protective effects of ischemic preconditioning for different periods of time and to elucidate the optimal safe ischemic preconditioning time for renal ischemia-reperfusion (I/R) injury in mice. METHODS: A total of 25 male C57BL/6 mice were randomly divided into 5 groups (sham, I/R, ischemic preconditioning [IP]-3, IP-5, and IP-7 groups), in which the kidney was preconditioned with IP of various durations and then subjected to I/R injury (the last 3 groups). To induce renal ischemia, the left renal pedicle was occluded with a nontraumatic microaneurysm clamp for 30 minutes followed by reperfusion for 24 hours. The effects of IP on renal I/R injury were evaluated in terms of renal function, tubular necrosis, apoptotic cell death and inflammatory cytokines. RESULTS: Results indicated that BUN and creatinine (Cr) levels increased significantly in the I/R group, but the elevations were significantly lower in IP groups, especially in the IP-5 group. Histological analysis revealed that kidney injury was markedly decreased in the IP-5 group compared with the I/R group, as evidenced by reduced renal necrosis/apoptosis. In addition, IP significantly inhibited gene expression of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) and chemokines (monocyte chemoattractant protein-1). Western blot analysis indicated that the expression levels of Toll-like receptor 4 (TLR4) and nuclear factor-kappa B (NF-κB) were upregulated in the I/R group, while expression was inhibited in the IP groups. CONCLUSION: Five-minute IP had the greatest protective effect against I/R injury.